Penggunaan Isu Sosiosaintifik Dalam Pembelajaran IPA: Review Literatur - Monaliza Rahma Putri; Miterianifa Miterianifa (Mahesa Research Center, 2023)
Socioscientific issues in the field of social sciences and science are issues that describe social problems in society and are related to conceptual, procedural, or scientific technological contexts. The purpose of this research is to describe how socioscientific issues are used in science learning. This review is a systematic literature review method. A systematic literature review is a method for evaluating, defining, and interpreting all results related to a research problem in response to specific questions. This literature review was conducted to obtain the publication of scientific articles in 2018-2023 that discuss socioscientific issues in science learning. Based on research results using socioscientific issues in science learning can increase scientific literacy and student learning activities so that they can trigger student discussion and argumentation which in turn increases critical thinking skills.